Hubungan Sosial Ekonomi dengan Penggunaan Alat Kontrasepsi Jangka Panjang (MKJP) di Puskesmas Labuhan Deli Kecamatan Labuhan Deli Kabupaten Deli Serdang Kecamatan Labuhan Deli Kabupaten Deli Serdang - Sonia Novita Sari; Sumihar Ernawaty Sirait; Imarina Tarigan (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
The use of contraception is an action that helps individuals or married couples to achieve certain objectives, avoid unwanted births, get births that are truly desired, regulate the interval between pregnancies and control the time of birth in the husband and wife relationship. The aim of this research is to determine the socio-economic relationship with the use of long-term contraceptives (MKJP) at the Labuhan Deli Community Health Center. All acceptors who visited in May-June at the Labuhan Deli Community Health Center were 39 respondents. Data analysis using univariate, bivariate analysis. The results of this study show that there is a relationship between maternal knowledge about immunization and providing complete basic immunization to babies at the Penanggalan Community Health Center, Penanggalan District, Subulussalam City in 2023. It is hoped that there will be more questions from health workers or more use of existing facilities as input. to receive information about health, especially the use of MKJP